Structure-Borne Sound Suppression of a Strongly/Weakly Excited Curved Panel Using a Quadratic Nonlinear Resonance Effect - Yiu-Yin Lee (Axioms)
This study aimed to investigate the structure-borne sound suppression of a strongly/weakly excited curved panel. Quadratic nonlinear resonance can induce anti-symmetric modal responses to replace symmetric modal responses, even though the physical panel dimensions and excitation distribution are symmetric. Unlike cubic nonlinear resonance, quadratic nonlinear resonance can be induced regardless of whether the panel vibration amplitude is small or large. As the sound radiation efficiency of anti-symmetric responses is much lower than that of symmetric responses, this quadratic nonlinear resonance effect is thus used for sound suppression. A set of multimode formulations was developed from the nonlinear structural governing equation and sound radiation efficiency equation. The quadratic nonlinear resonant responses and some other nonlinear responses were computed from the multimode formulations. Modal convergence studies and parametric studies were performed to understand the effects of various parameters on the quadratic nonlinear responses and sound suppression. The results showed that when the panel was strongly excited, the difference between the peak sound levels in the linear and nonlinear cases was up to 12 dB, and when the panel was weakly excited, the difference was up to 6 dB.